Diagnóstico da cadeia produtiva de caprinos e ovinos no Brasil - Maicon Gonçalves Monteiro; Marlon Vinícius Brisola; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– Brazilian agribusiness, a sector that represents a quarter of the country's economy, has undergone significant transformations since the 1960s. With the economic opening and financial stabilization of the 1990s, several agribusiness productive segments maintained a good performance, although the supply chain goats and sheep, in particular, faced difficulties in their trajectory. Thus, this study, by means of the description, sought to make a diagnosis of the agro-industrial complex of goat breeding in Brazil, highlighting its main limitations, demands and advances. It was identified that the main problems stem from the informality present in the sector, the lack of private policies and actions that promote the training of producers, the support to production activities and the unsustainability in the commercialization of products derived from integrated actions between producers and between public and private. Important actions already taken in the sector were highlighted, such as the Rota do Cordeiro and the formation of producer cooperatives.
Keywords: O13; Q01; Q18; 330; agribusiness; public policy; caprinovinoculture